Pemikiran Hermeneutika Al-Qur’an Hasan Hanafi dalam Studi Al-Qur’an di Indonesia - Mubaidi Sulaeman (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
The hermeneutics built by Hasan Hanafi used four scientific foundations from Islam and the West Thougt, namely ushul fiqh, phenomenology, Marxism, and hermeneutics itself. By using these four ingridients, Hasan Hanafi built a hermeneutic theory capable of accommodating the idea of ​​liberation in Islamic revolutionary interpretation which is capable of being a normative-ideological foundation for Muslims to face all forms of repression, exploitation and injustice, both from within and without. This is applied to the study of the Qur'an among Liberal Muslims in Indonesia by interpreting the verses of the Qur'an which prohibit interfaith marriages in a hermeneutic way. Where their interpretation of the verses of the Al-Qur'an surah Al-Baqarah verse 221, is only temporal and valid in his day, because he has been transformed by the verse that came after him, namely the letter Al-Maidah verse 5, which allows different marriages to occur religion. The law that prohibits interfaith marriage because of its position as law that was born out of the ijtihad process, it is very possible if a new opinion is made, that Muslim women can marry non-Muslim men, or interfaith marriages more broadly, regardless of their religion or belief